Studies on the genus Rhyparus Westwood, 1845 (Coleoptera: Scarabaeidae: Aphodiinae) with description of five new species from Southeast Asia - Minkina, Łukasz (Zootaxa, 2026)
Five new Rhyparus Westwood, 1845 species from Southeast Asia are described and illustrated: Rhyparus banyuwangiensis Minkina, sp. nov. from Indonesia (Java), R. crockerrangensis Minkina, sp. nov. from Malaysia (Borneo), R. edelmani Minkina, sp. nov. from Indonesia (Sulawesi), R. halmaheraensis Minkina, sp. nov. from Indonesia (Halmahera) and R. krikkeni Minkina, sp. nov. from Indonesia (Sulawesi). Rhyparus breviceps Paulian, 1984 is reported for the first time from the island of Sulawesi—the population there differs slightly from the typical specimens, as discussed.